Acquisition of Indonesian Sentences in Children's Language Development (LITPAM, 2025)
This study generally aims to investigate Indonesian sentence acquisition and use in early childhood. The data in this study was obtained from the speech of early childhood children in Wisma Kerta Village, Karangasem Regency, Bali Province. The data collection methods and techniques in this study are participation observation, listening, and recording methods, with note-taking techniques. The data are analyzed qualitatively and descriptively. The theory of language acquisition in early childhood by Brown (2007) is applied to examine sentence acquisition, and the theory of the realm of language use by Fishman (1968) is applied to analyze the use of language in various domains. The results of this study showed that early children had acquired sentence acquisitions in the form of negation sentences, interrogative sentences, and no passive voice. At the age of 5-6 years, the child was able to articulate each sound clearly. The sentences acquired were interrogative, declarative, imperative, and passive sentences. The use of language in family, neighborhood, work, and religion domains by early childhood used informal forms. The use of the Balinese language and its dialects were found in several utterances in each domain.